Análisis Social Y Jurídico De Los Consumidores De Sustancias Estupefacientes Y Psicotrópicas Con El Fin De Disminuir La Delincuencia - Salvador Elizalde, Juan José (2011)
There is consensus to maintain that in the late 20th century and early of the present century, the phenomenon of the revaluation of Human Rights it constitutes an unquestionable fact. Human Rights recognize its origin in the French Revolution, specifically in the Declaration of Human Rights, an instrument that recognized certain rights to all human beings for their quality as such. The universality that Human Rights have acquired, makes them constitute heritage of all the world geography.